Characterization of femtosecond-laser pulse induced cell membrane nanosurgical attachment - Katchinskiy, Nir (Biomed Opt Express, 2016)
This article provides insight into the mechanism of femtosecond laser nanosurgical attachment of cells. We have demonstrated that during the attachment of two retinoblastoma cells using sub-10 femtosecond laser pulses, with 800 nm central wavelength, the phospholipid molecules of both cells hemifuse and form one shared phospholipid bilayer, at the attachment location. In order to verify the hypothesis that hemifusion takes place, transmission electron microscope images of the cell membranes of retinoblastoma cells were taken. It is shown that at the attachment interface, the two cell membranes coalesce and form one single membrane shared by both cells. Thus, further evidence is provided to support the hypothesis that laser-induced ionization process led to an ultrafast reversible destabilization of the phospholipid layer of the cellular membrane, which resulted in cross-linking of the phospholipid molecules in each membrane. This process of hemifusion occurs throughout the entire penetration depth of the femtosecond laser pulse train. Thus, the attachment between the cells takes place across a large surface area, which affirms our findings of strong physical attachment between the cells. The femtosecond laser pulse hemifusion technique can potentially provide a platform for precise molecular manipulation of cellular membranes. Manipulation of the cellular membrane is an important procedure that could aid in studying diseases such as cancer; where the expression level of plasma proteins on the cell membrane is altered.